Legal Certainty for the Implementation of Execution in the Form of Payment of Money in Lieu of Corruption Cases in the Criminal Justice System - Erwinda Emran, Nevertiti; Lina, Ramlani; Ismed, Mohamad (Jurnal Multidisiplin Indonesia, 2024)
The determination of additional punishment in the form of "replacement money" should ideally be equivalent or balanced with the state financial losses as a result of criminal acts of corruption. The formulation of the problem in writing this thesis is how to execute replacement money for criminal acts of corruption according to positive law and what is the legal certainty of execution in the form of payment of replacement money for corruption cases in the criminal criminal system. The research method used in this research is normative juridical, with a statutory, conceptual and case approach. The legal materials used are primary, secondary and tertiary legal materials and the analysis of legal materials is qualitative. The research results show that one of the elements of corruption in Article 2 and Article 3 of Law 31/1999 jo. Law 20/2001 is a loss to state finances. This element has the consequence that eradicating corruption does not only aim to deter corruptors through imposing heavy prison sentences, but also restore state finances due to corruption, as emphasized in the General Precautions and Explanation of Law 31/1999. By law, the instrument to restore state finances is included in the additional penalty in the form of payment of replacement money. The difference in the meaning of the criminal purpose of paying replacement money between what is intended in the explanation of the Law and the formulation of Article 18 paragraph (1) letter b causes the purpose of paying replacement money to be unclear. This ambiguity also has an impact on the dualism in the application of calculating the value of replacement money as seen in several Supreme Court (MA) decisions. The legal umbrella for execution in this case is Article 18 of Law 31/1999 and not the Supreme Court's fatwa. The execution of replacement money also does not require a separate lawsuit, because the additional crime of replacement money is a single criminal decision handed down by a panel of judges, where the authority to execute each criminal decision, both main and additional crimes, rests with the public prosecutor. The need for the Supreme Court's fatwa should not be for carrying out executions but as a legal umbrella for how long a substitute prison sentence will be served if the compensation money has been paid in part, which is currently not regulated in Law 31/1999 jo. Law 20/2001 and other derivative regulations.